Critical perspectives on white supremacy and racism in Canadian education: dispatches from the field - Kempf, Arlo (Critical perspectives on teaching and teachers' work, 2024)
"Critical Perspectives on White Supremacy and Racism in Canadian Education shows how K-12 schooling continues to product and maintain white supremacist and colonial logics, and questions alternate future for schooling in Canada. It argues that white supremacy and race in schooling are present in colonial-centered approaches to teacher education, formal and informal exclusion through curriculum development, and persistent failed commitments to multiculturalism. These themes guide the organization of this collection, which is further underpinned by theoretical perspectives including critical race theory, anti-Blackness theory, and anticolonial theory. Contributions are drawn from classroom teachers, community educations and pre-service teacher educators, and are powerfully informed by first-hand accounts as well as stories of teachers and teacher candidates. Combining theory with practice, this edited volume will be important reading for advanced undergraduate and postgraduate students in Social Justice Education, Multicultural Education, and Indigenous Studies. It will also be beneficial reading for Antiracist and Indigenous Education researchers, as well as policymakers and practitioners within Critical Education"--